2020
DOI: 10.1158/1078-0432.ccr-20-1831
|View full text |Cite
|
Sign up to set email alerts
|

Neratinib-Plus-Cetuximab in Quadruple-WT (KRAS, NRAS, BRAF, PIK3CA) Metastatic Colorectal Cancer Resistant to Cetuximab or Panitumumab: NSABP FC-7, A Phase Ib Study

Abstract: Dr. Sama reports employment and stock options with Bristol Myers Squibb Ms. Piette reports commercial agreement to perform the statistical analyses, to participate in the writing of the statistical section of the manuscript, and the review. Dr. Pogue-Geile reports grants from the NCI and the Pennsylvania Dept of Health (PA DoH), during the conduct of the study*, and from Puma Biotechnology, Inc. (Puma). Mr. Lipchik reports grants to his institution from the PA DoH,* and Puma. Ms. Finnigan reports grants to her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In two large clinical studies, trastuzumab and lapatinib/pertuzumab combinations showed good activity and tolerability in EGFR-resistant HER2-positive mCRC [ 74 , 75 ]. However, data from a recently published Phase Ib clinical study suggest that neratinib-plus-cetuximab did not show an objective response in quadruple-WT (KRAS, NRAS, BRAF and PIK3CA) mCRC resistant to cetuximab or panitumumab [ 73 ].…”
Section: Aberrant Activations Of Alternative Receptorsmentioning
confidence: 99%
“…In two large clinical studies, trastuzumab and lapatinib/pertuzumab combinations showed good activity and tolerability in EGFR-resistant HER2-positive mCRC [ 74 , 75 ]. However, data from a recently published Phase Ib clinical study suggest that neratinib-plus-cetuximab did not show an objective response in quadruple-WT (KRAS, NRAS, BRAF and PIK3CA) mCRC resistant to cetuximab or panitumumab [ 73 ].…”
Section: Aberrant Activations Of Alternative Receptorsmentioning
confidence: 99%
“…Jacobs et al reported the results of a phase Ib clinical trial involving 11 patients with RAS/BRAF/PIK3CA WT; ERRB2-positive tumors were treated with neratinib and cetuximab. However, it did not show responses: seven received stable disease, four of whom had ERBB2 amplification either in the primary tumor or the enrolment biopsy [ 77 ].…”
Section: Clinical Trials For Patients With Erbb2-positive Mcrcmentioning
confidence: 99%
“…Only one in 7 patients had dose-limiting toxicity (G3 diarrhoea), although 67% had G3 AEs. Drug-related AEs of special interest were diarrhoea, rash and elevated transaminases [43].…”
Section: Dual Monoclonal Antibodiesmentioning
confidence: 99%